Breaking the Chains of Submissiveness: A Review of Female Empowerment in Ibsen’s ‘A Doll’s House’ (International Journal of Food and Nutritional Sciences, 2022)
This paper explores the theme of female submission in Henik Ibsen’s “A Doll’s House”.Through a critical analysis of the protagonist, Nora Helmer, it argues that Nora’s journeychallenges societal expectations of female submissiveness